Process compensated bipolar junction transistor‐based CMOS temperature sensor with a ±1.5°C (3σ) batch‐to‐batch inaccuracy. Issue 22 (1st November 2018) - Sun, Dapeng; Zhang, Tan‐Tan; Law, Man‐Kay; Mak, Pui‐In; Martins, Rui Paulo
Abstract : A bipolar junction transistor (BJT)‐based CMOS temperature sensor exploiting the piecewise BJT process spread compensation property of the base recombination current is proposed to reduce the process variations of the base–emitter voltage ( V be ). The weighted combinations of different on‐chip resistors are explored to minimise their associated process spread. Fabricated in standard 0.18‐μm CMOS, the chip prototype occupies an active area of 0.036 mm 2 and draws 3 μA from a 1.2 V supply, with a measured maximum inter‐/intra‐die variation in V be of <1.5 mV from −40 to 125°C from two batches. Using the measured V be, Δ V be and the first‐batch‐only calibration parameters, the chip prototype demonstrates an untrimmed batch‐to‐batch inaccuracy of ± 1.5°C (3 σ ) within the same temperature range (24 samples from 2 batches).